Urinary Cypermethrin Metabolites among Conventional and Organic Farmers in Thailand - Tremongkoltip A. (2023)
Cypermethrin, a pyrethroid insecticide, is frequently spread on agricultural farmlands and is also used in households in Thailand. Conventional pesticide-using farmers (n = 209) were recruited from the Phitsanulok and Nakornsawan provinces. Certified organic farmers (n = 224) were also recruited in the Yasothorn province. The farmers were interviewed via a questionnaire and the urine from their first morning void was collected. The urine samples were analyzed for 3-phenoxybenzoic acid (3-PBA), cis-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid (cis-DCCA), and trans-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid (trans-DCCA). The results showed no significant difference in the urinary cypermethrin metabolites between the conventional farmers and the organic farmers, for whom the usage of cypermethrin was not accounted for. However, when conventional farmers who used cypermethrin on the farm and in the home were compared with conventional farmers who did not use any cypermethrin or with organic farmers, a significant difference was noted for all metabolites except for trans-DCCA. These findings show that the most significant exposures to cypermethrin are among conventional farmers who use the insecticide on their farms or in their homes. However, measurable levels of all metabolites were found among both conventional and organic farmers who only used cypermethrin in the home or not at all, suggesting that the at-home use of pyrethroids and other possible exposures from pyrethroid residues on market-bought food may contribute to urinary levels of pyrethroids that exceed those of the general population in the US and Canada.